Bidirectional rotating flow of nanofluid over a variable thickened stretching sheet with non-Fourier's heat flux and non-Fick's mass flux theory. - Fazle Mabood; Maria Imtiaz; Maimona Rafiq; Essam Roshdy El-Zahar; Maawiya Ould Sidi; Muhammad Ijaz Khan (PLoS ONE, 2022)
The flow of nanofluid over a variable thickened stretching sheet is studied in this article. Non-Fourier's heat flux and non-Fick's mass flux are incorporated for heat and mass flow analysis. Silver (Ag) and Copper (Cu) are considered nanoparticles with water as base fluid. The resulting equations are transformed into the dimensionless form using similarity transformation and solved by RK-4 with the shooting method. The impact of the governing parameters on the dimensionless velocity, temperature, concentration, skin friction coefficient, streamlines, and finally isotherms are incorporated. It is observed that increment in power-law index parameter uplifts the fluid flow, heat, and mass transfer. The increase in the magnitude of skin friction coefficient in (x-direction) with wall thickness parameter is high for nanofluid containing silver nanoparticles as compared to copper nanoparticles.